Answer:
D. 5x^2-4
Explanation:
We are asked to find (f+g)(x), which is really just the sum of the two functions.
(f+g)(x)=f(x)+g(x)
We know the the functions are:
• f(x)= 4x^2+1
• g(x)=x^2-5
Substitute the functions in.
(f+g)(x)=(4x^2+1)+(x^2-5)
Add the functions by combining like terms. For this equation, the like terms are those with x^2 and the constants.
(f+g)(x)= (4x^2+x^2)+(1-5)
Add the terms with x^2
(f+g)(x)=(5x^2)+(1-5)
Add the constants or terms without variables.
(f+g)(x)=(5x^2)+(-4) = 5x^2-4
The sum of the functions is D. 5x^2-4